Respuesta :
Step-by-step explanation:
1) 7b – 37 = 4(5b - 6)
7b - 37= 20b - 24
-13b = 13
dividing both sides by -13
b=-13/13=-1
b = -1
Answer and Step-by-step explanation:
[tex]\Huge \boxed{b=-1}.[/tex]
Step 1 : Simplify both the sides of the equation :
[tex]7b-37=4(5b-6)\\7b+-37=(4)(5b)+(4)(-6)\\7b+-37=20b+-24\\7b-37=20b-24[/tex]
Step 2 : Subtract 20b from both sides :
[tex]7b-37-20b=20b-24-20b\\-13b-37=-24[/tex]
Step 3 : Add 37 to both sides :
[tex]-13b-37+37=-24+37\\-13b=13[/tex]
Step 4 : Divide both sides by -13 :
[tex]\frac{-13b}{-13}=\frac{13}{-13}[/tex]
[tex]b=-1[/tex]
That's our final answer !